PENYULUHAN INFORMASI OBAT PENYAKIT ASAM URAT - Maulana Tegar AdityaNugraha (LPPM STIKES Madani Yogyakarta, 2021)
This community service activity is an activity carried out by Health Sciences College Madani Yogyakarta lecturers assisted by education staff to further improve science in the pharmaceutical field, especially information on gout drugs. This activity is carried out as a form of the Tri Dharma of Higher Education, it’s caled community service that is carried out regularly. Health Sciences College Madani Yogyakarta is continous carries out health counseling which is used as a forum for community service to improve health levels. The method of this activity is carried out in three stages, they are preparation, implementation and evaluation. The preparation stages include field observations, collection of materials and preparation of materials about drug’s gout information and coordination with related parties. The implementation stages this activity is gathering participants at the counseling location, then giving health education about information and gout treatment. At the evaluation stage is preparation of reports and positive follow-up of improving health and knowledge about gout.